2013
DOI: 10.1142/s179354581350003x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Structure–activity Relationship Study of Heptamethine Indocyanine Dyes for Tumor-Targeted Imaging

Abstract: Our research has identi¯ed a couple of near-infrared (NIR) heptamethine indocyanine dyes exhibiting preferential tumor accumulation property for in vivo imaging. On the basis of our foregoing work, we describe here a preliminary structureÀactivity relationship (SAR) study of 11 related heptamethine indocyanine dyes and several essential requirements of these structures for in vivo tumor-targeted imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…They exhibit to retain preferentially in a broad‐spectrum of cancer cells and accumulate at cellular mitochondria. Our structure‐activity relationship study and other reports also indicate that the heptamethine core with lipophilic cationic property is essential for mitochondrial targeting and imaging. In addition, certain cyanine dyes have been demonstrated with photosensitization effects, which are closely associated with their lipo‐hydro partition coefficients (log P ), polarizabilities, and molar absorption coefficients .…”
Section: Introductionsupporting
confidence: 78%
“…They exhibit to retain preferentially in a broad‐spectrum of cancer cells and accumulate at cellular mitochondria. Our structure‐activity relationship study and other reports also indicate that the heptamethine core with lipophilic cationic property is essential for mitochondrial targeting and imaging. In addition, certain cyanine dyes have been demonstrated with photosensitization effects, which are closely associated with their lipo‐hydro partition coefficients (log P ), polarizabilities, and molar absorption coefficients .…”
Section: Introductionsupporting
confidence: 78%
“…In our recent work, we have identified a class of lipophilic NIR fluorescent heptamethine cyanine dyes, which are able to preferentially accumulate into cell mitochondria and possess unique optical properties for in vivo cell tracking and biomedical imaging . Our structure–activity relationship study and other reports have indicated that the heptamethine core with lipophilic cationic property is essential for mitochondrial targeting. Based on these foregoing studies, in this work, we designed and synthesized a series of heptamethine dyes modified with various N ‐alkyl side chains around the heptamethine core, and successfully developed a new derivative, termed NIR cell protector‐61 (NIRCP‐61), which maintains the superior optical imaging properties and significantly decreases the cell contamination.…”
Section: Introductionmentioning
confidence: 65%
“…They have been extensively explored to probe aspects of mitochondrial physiology, including mitophagy, membrane potential, pH, polarity, glutathione, cysteine, ROS, and nitroreductase activity [ 4 , 63 ]. Apparently, the heptamethine core of cyanine dyes plays a key role in mitochondrial targeting [ 63 , 64 , 65 ]. Some cyanine dyes can serve as PSs, which may be related to their molar absorption coefficients, polarizability, and lipo-hydropartition coefficients [ 66 , 67 ].…”
Section: Strategies For Mitochondria-targeted Ptmentioning
confidence: 99%